Relasi Israel dan Gereja - Deni Telaumbanua (TE DEUM (Jurnal Teologi dan Pengembangan Pelayanan), 2019)
Israel and church relations are generally seen in two opposite poles. At the first pole the Parentesis's view maintains the difference. At other poles the view of Covenantalis saw the unity of both. The main thesis of this article is the relationship between Israel and the church, that in the end there is only one Israelite or one church to be saved. It was evidenced through the elaboration of Romans 9-11. The Apostle Paul analogize the unity of Israel and the church with the dough and olive trees. In the end, the olive tree consists of a wild bud that is grafted (not Israel) and the original shoots (' All-Israel ' stubborn) are remade. From the description, at the end of this article, the author outlines the relationship application between Israel and the church against some other Christian doctrines, such as: Christology, Soteriology, Ecclesiology, eschatology, and in the practical life of people Christian.